A Comparative Study of Endometriosis and Normal Endometrium Based on Ultrasound Observation. (30th April 2022) - Jiao, Lin; Wang, Jue; Zhu, Lingling
Abstract : In order to compare the microscopic ultrastructure of eutopic endometrium and normal endometrium in patients with endometriosis, to study the specific pathogenesis of endometriosis. In this paper, on the basis of using B-ultrasound technology, several patients with endometriosis were subjected to B-ultrasound to observe the ultrastructure of the eutopic uterine endometrium and compared with the pictures of normal endometrium to carry out the specific analysis between the two ultrastructural comparisons. This study is based on the analysis of B-ultrasound images of patients with endometriosis, compares the difference between their ultrastructure and normal human body, and conducts specific pathological diagnosis and analysis to find out the impact of the endometrium in place. The specific factors of the occurrence of lesions and the corresponding treatment methods are proposed. The experimental results show that the ultrastructure of endometriosis eutopic endometrium is different from that of normal endometrium. The microvilli of secretory cells and the cilia of ciliated cells of the former are abnormally increased and lengthened, and they are superior to B-ultrasound technology. The success rate of the examination is 93.75%, which can play an important role in the specific examination process of patients with endometriosis, as one of the actual indicators of detection. Under the electron microscope, microvilli are tiny finger-like protrusions extending from the cell membrane and the cytoplasm on the free surface of the cell, surrounded by the cell membrane and perpendicular to the cell membrane surface.